2021
DOI: 10.1186/s12936-021-03992-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of malaria testing at health facilities: the case of Uganda

Abstract: Background The World Health Organization (WHO) recommends prompt malaria diagnosis with either microscopy or malaria rapid diagnostic tests (RDTs) and treatment with an effective anti-malarial, as key interventions to control malaria. However, in sub-Saharan Africa, malaria diagnosis is still often influenced by clinical symptoms, with patients and care providers often interpreting all fevers as malaria. The Ministry of Health in Uganda defines suspected malaria cases as those with a fever. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Increased supplies of rapid diagnostic tests would allow for more consistent testing prior to antimalarial treatment. Indeed, it has been shown in several studies that the ready availability of testing is a major factor in adherence to the "test and treat" strategy recommended by the WHO [4,[10][11][12][13][14]. Similarly, improved nursing ratios and adequate artesunate supply would allow for more timely administration of medications as well as closer monitoring of patient status.…”
Section: Provide Oxygenmentioning
confidence: 99%
“…Increased supplies of rapid diagnostic tests would allow for more consistent testing prior to antimalarial treatment. Indeed, it has been shown in several studies that the ready availability of testing is a major factor in adherence to the "test and treat" strategy recommended by the WHO [4,[10][11][12][13][14]. Similarly, improved nursing ratios and adequate artesunate supply would allow for more timely administration of medications as well as closer monitoring of patient status.…”
Section: Provide Oxygenmentioning
confidence: 99%
“…Uganda, ranking fifth in African malaria cases, faces an annual incidence rate of 478 cases per 1,000 people, impacting outpatient visits, hospital admissions, and fatalities [4] [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that multiple blood cultures (>3), yield sensitivities of 73–97%, particularly larger volume (10–30 ml) [ 15 ]. Despite though, it is not routine in Uganda to obtain the mandatory three blood samples in the paediatric population and such results are often not timely available to guide prescriptions due to a backlog of samples amidst scarce human and infrastructural resources [ 17 ].…”
Section: Introductionmentioning
confidence: 99%